Pengaruh Pola Anyaman terhadap Perilaku Lentur Textile Reinforced Concrete (TRC) dengan Perkuatan Serat Rami: The Effect of Woven Patterns on Flexural Behaviour of Textile Reinforced Concrete (TRC) with Ramie Fiber Reinforcement - Arief Budiman; Erizal (Jurnal Teknik Sipil dan Lingkungan, 2021)
The demand of concrete has increased in Indonesia. A reinforced concrete innovation being developed is Textile Reinforced Concrete (TRC). Ramie fiber has great potential to be used as a construction material because it has advantages over other natural fibers, such as tensile strength properties. The research aims to analyzed flexural behaviour of Ramie fiber TRC. This research was conducted from February until June 2021 at IPB University. The research was carried out through several stages, that are testing of TRC materials, mix design, weaving and coating ramie fiber, manufacturing and curing test objects, and testing. The flexural behavior analyzed flexural strength, stiffness, ductility, and crack behavior. Ramie fiber reinforcement can improve the elasticity and ductility of mortar plates. However, woven ramie fiber with a certain woven pattern can reduce flexural strength. Coating ramie fiber with Unsaturated Polyester Resin (UPR) provides an increase in flexural strength, elastic properties, and ductility. Phases of crack behaviour of UPR-coated are uncracked, crack formation, crack stabilization, and failure. The woven pattern that produces the highest flexural strength is the two-axis woven pattern for UPR-coated ramie, which is 7.84 MPa.